2008
DOI: 10.1200/jco.2007.15.2348
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Specific Differences in Outcome of Squamous Cell Carcinoma of the Anal Canal: A Multicentric Cohort Study of HIV-Positive Patients Receiving Highly Active Antiretroviral Therapy

Abstract: Long-term LC and acute toxicity represent major clinical challenges in HIV-positive patients with anal carcinoma. Even if fluoropyrimidine-based CRT is feasible and may result in similar response rates and OS as in HIV-negative patients, improved treatment strategies with better long-term outcome are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
134
3
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(164 citation statements)
references
References 35 publications
10
134
3
7
Order By: Relevance
“…There was a discrepancy in the number of patients with SCC of the anus in the HIV positive cohort (68%) compared to the number of patients in the HIV negative cohort (31%). This supports past findings that HIV positive individuals have a higher risk of developing anal SCC than HIV negative individuals [4,5,[15][16][17].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…There was a discrepancy in the number of patients with SCC of the anus in the HIV positive cohort (68%) compared to the number of patients in the HIV negative cohort (31%). This supports past findings that HIV positive individuals have a higher risk of developing anal SCC than HIV negative individuals [4,5,[15][16][17].…”
Section: Discussionsupporting
confidence: 82%
“…Specifically, the 5-year survival rates for HIV negative and HIV positive patients were 57% and 58%, respectively, which is not significantly different. Other retrospective cohort studies have demonstrated similar 5-year survival rates (61%-71%) in HIV positive patients [16,18,19,20]. In 1996, before the widespread use of HAART, poorer outcomes were demonstrated with HIV positive patients with anal SCC.…”
Section: Discussionmentioning
confidence: 69%
“…Similarly to other studies (17)(18)(19)(20), we also demonstrated that tumor size, nodal status and HIV status are the most significant prognostic factors for patients with anal SCC. On multivariate analysis, patients with tumors >5 cm as well as those with HIV+ had almost 3 times more risk of developing a disease event and at least 4 times the risk of dying from anal cancer.…”
Section: Discussionsupporting
confidence: 61%
“…This excess of mortality is probably imputable to various factors that continue to distinguish HIV-infected patients from the general population even during the HAART era: a more advanced cancer stage at diagnosis, 11,12,[18][19][20] a more aggressive cancer behavior 33 and a higher proportion of concomitant comorbidities (especially viral hepatitis and related hepatic impairment).…”
Section: 1%)]mentioning
confidence: 99%